Finance and Development, September 2019. (Finance and Development; Finance and Development ;, 2019)
This issue of Finance and Development focuses on dark web of secret transactions that enable tax evasion and avoidance, money laundering, illicit financial flows, and corruption. Demands on government resources are building-to boost growth in some advanced economies, build infrastructure in emerging markets, and improve health and education in the developing world. IMF research shows that countries with lower levels of perceived corruption have significantly less waste in public projects. Among low-income countries, the share of the budget dedicated to education and health is one-third lower in more corrupt countries. The rise of digital finance, crypto assets, and cybercrime adds to the challenges. Consider the so-called dark web, a hidden marketplace for everything from stolen identities to arms and narcotics. Improving governance is not easy; it requires sustained effort over the long term.